Analysis and Design of a Crowdsourcing-Based Flooded Road Reporting Sys-tem Indonesia (FROSTID) Application - Eka Prakarsa Mandyartha; Asif Faroqi (Nusantara Science and Technology Proceedings, 2020)
The problem of flooded road infrastructure mainly occurs in urban areas, due to low soil bearing capacity, high rainfall intensity, and failure of rainwater flow to the drainage system. Flooded roads, when traversed by motorized vehicles, will be very detrimental to the rider. Flood water can damage engines, transmissions, electrical components, and motor vehicle electronic computer systems. Water is also very dangerous to car safety devices, such as airbags and braking systems that use ABS (Antilock Braking System). Also, there may be health problems involving fungi and bacteria, due to damp vehicles, especially on cars. Other problems related to water may not be immediately apparent, such as rust and corrosion, which will develop over time. The flooded road reporting system is an early warning system that provides information to road users so they can take anticipatory steps. This research proposes a crowdsourcing-based flood road reporting system, called Frostid (Flooded Road Reporting System Indonesia), that involves local road users in collecting flood information. Frostid application users can not only access geospatial information for flooded roads but also can collect location data using the Global Positioning System (GPS) and upload the location points of flooded roads using their smartphones. The Frostid application uses a navigation map to describe the location of flooded roads. Flood information stored in the Frostid application is built entirely by local road users. The Frostid application is built on a mobile Android platform.